1) х² - 9х+14 = 0
Выделим полный квадрат: х² - 9х+14 = х² - 2*4,5х + 4,5² - 4,5² +14 =
= (х - 4,5)² - 20,25 + 14 = (х - 4,5)² - 6,25 = (х - 4,5)² - 2,5² =
= (х - 4,5 - 2,5)(х - 4,5 + 2,5) = (х - 7)(х - 2) => уравнение имеет вид:
(х - 7)(х - 2) = 0
х - 7 = 0 или х - 2 = 0
х = 7 или х = 2
ответ: 2; 7.
2) х²+5х - 14 = 0
Выделим полный квадрат: х²+5х - 14 = х² + 2*2,5х + 2,5² - 2,5² - 14 =
= (х + 2,5)² - 6,25 - 14 = (х + 2,5)² - 20,25 = (х + 2,5)² - 4,5² =
= (х + 2,5 - 4,5)(х + 2,5 + 4,5) = (х - 2)(х + 7) => уравнение имеет вид:
(х - 2)(х + 7) = 0
х - 2 = 0 или х + 7 = 0
х = 2 или х = -7
ответ: 2; - 7.
2x+7x+10=0
9x+10=0
9x=-10
x=(-10)÷9
x=-10/9
2) -x2+8x-52=0
-2x+8x-52=0
6x-52=0
6x=52
x=52÷6
x=26/3
3) -x2-4x-3=0
-2x-4x-3=0
-6x-3=0
-6x=3
6x=-3
x=(-3)÷6
x=-1/2
4) -x2-14-50=0
x=-32
5) x2-12x+29=0
x=29/10
6) -x2+4x+5=0
x=-5/2
7) -x2+8x-9=0
x=3/2
8) x2-4x-2=0
x=-1
9) x2+3x-4=0
x=4/5
10) x2-14x+49=0
x=49/12
11) x2+4x+20=0
x=-10/3